A framework for assessing ecosystem services in acequia irrigation communities of the Upper Río Grande watershed. (8th June 2015) - Raheem, N.; Archambault, S.; Arellano, E.; Gonzales, M.; Kopp, D.; Rivera, J.; Guldan, S.; Boykin, K.; Oldham, C.; Valdez, A.; Colt, S.; Lamadrid, E.; et al.
<x xml:space="preserve">Abstract</x> 'What we need to do is inventory the different types of agricultural landscapes and bring to light the typical rural architecture, such as the acequias and desagües (irrigation supply canals and excess water drains). We need to find ways of conserving the landscape, including the flora and fauna as well as the role the agricultural landscape has played in the evolution of the surrounding area. Before we abandon the past (flood irrigation) for the contemporary (drip irrigation), we need a thorough analysis of the pros and cons of each system for the whole cultural landscape. The future may be one where the old and new learn to coexist, such as the hoe with the plow' (Arellano, 2014, p. 204). WIREs Water 2015, 2:559–575. doi: 10.1002/wat2.1091 For further resources related to this article, please visit the WIREs website.